Disruption of Myc-Tubulin Interaction by Hyperphosphorylation of c-Myc during Mitosis or by Constitutive Hyperphosphorylation of Mutant c-Myc in Burkitt's Lymphoma - Niklinski, Jacek (American Society for Microbiology, 2000)
Somatic mutations at Thr-58 of c-Myc have been detected in Burkitt's lymphoma (BL) tumors and have been shown to affect the transforming potential of the Myc oncoprotein. In addition, the N-terminal domain of c-Myc has been shown to interact with microtubules in vivo, and the binding of c-Myc to α-tubulin was localized to amino acids 48 to 135 within the c-Myc protein. We demonstrate that c-Myc proteins harboring a naturally occurring mutation at Thr-58 from BL cell lines have increased stability and are constitutively hyperphosphorylated, which disrupts the in vivo interaction of c-Myc with α-tubulin. In addition, we show that wild-type c-Myc–α-tubulin interactions are also disrupted during a transient mitosis-specific hyperphosphorylation of c-Myc, which resembles the constitutive hyperphosphorylation pattern of Thr-58 in BL cells.